CHARACTERISTICS OF EMPATHY IN ADOLESCENCE (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article explores the nuanced characteristics of empathy during adolescence, a critical developmental period marked by profound social, emotional, and cognitive changes. Drawing from a review of relevant literature, the study delves into the key components that shape adolescent empathy, examining factors such as cognitive empathy, emotional regulation, and social context. The findings contribute to a better understanding of how empathy manifests in adolescence and its implications for fostering positive social interactions and emotional well-being.